Athletic Technical Skills of Students as Training Efficiency Indicator - Sergey Barantsev; Elena Naidyonova; Vera Serygina; Irina Merkulova; Vladimir Myshyakov (OVS LLC, 2020)
The purpose of the study is to evaluate the effectiveness of training sessions among the 1st-3rd year students of the general physical training (GPT) volleyball groups. Materials and methods. The athletic technical skills (ATS) have been tested by results of tests on upper and lower passes and serves. ATS testing of students from GPT volleyball groups was carried out at the beginning and at the end of the spring semester, in which 45 of the 1st year students (2 study groups), 60 of the 2nd year students (3 groups), 33 of the 3rd year students (2 groups) took part. The same students took part in the testing at the beginning and at the end of the semester (pairwise comparison). Research result. The method to evaluate the effectiveness of practical training for the Program of "Physical Culture" has been developed. Special aspects of ATS indicators dynamics of the 1st-3rd year students of GPT educational groups with sports orientation (volleyball) from the beginning to the end of spring semester were revealed.  Conclusion. The highest efficiency of training sessions was observed among the 2nd year students. It is characterized by an increase in the number of students who successfully passed the tests on upper and lower passes by 5%, and 12%, respectively. The number of students who successfully passed the tests on serves increased by 11%, and a performance level grew from middle at the beginning of the semester to high at the end of the semester. The lowest effectiveness of training sessions was observed among the 1st year students. The outcome indicator of volleyball basic training corresponds to medium level at the beginning and at the end of the spring semester. The change in the number of students who successfully passed the tests on upper passes (-2%), lower passes (-2%), and serves (+2%) was insignificant from the beginning to the end of the semester.